DYNAMICS OF STRESS IN THE NEEDLE OF A KNITTING MACHINE WHEN INTERACTING WITH A WEDGE - ПЛЕШКО, С. А.; КОВАЛЬОВ, Ю. А. (Technologies and Engineering, 2024)
Objective. The purpose of this study is to develop a method for assessing the influence of stiffness of the needle-wedge pair of a knitting machine on the dynamics of stress that occurs in the needle rod when it hits the wedge. Methods. To resolve the tasks assigned for this study, modern methods of theoretical research based on the theory of propagation of stress waves in flat rod elements under longitudinal impact were used. Results. Given the expediency of increasing the life time of knitting machine needles by reducing the stress that occurs during their interaction with wedges, this article is devoted to the development of a method for assessing the influence of stiffness of the needle-wedge pair of a knitting machine on the dynamics of stress that occurs in the needle rod when it hits the wedge. Thus, this paper presents a method of assessing the influence of stiffness of the needle-wedge pair of a knitting machine on the dynamics of stress arising in the needle rod during its shock interaction with the knitting system wedges. The analysis of obtained dependencies showed that the needle-wedge pair stiffness affects the intensity of stress in the needle rod caused by the shock wave. At the same time, the reduction in stiffness helps to reduce the intensity of stress in the needle rod. The needle has a complex geometric shape. Therefore, when a needle hits a wedge, a complex field of stresses, which depends on the geometric shape of the needle, arises in its body. Equations presented in this study approximately describe the process of changing the stresses in the body of the needle when it hits the wedge. However, the results obtained allow us concluding that reducing the stiffness of the needle-wedge pair has a beneficial effect on increasing the life time of knitting needles. Originality. The development of scientific foundations and engineering methods of designing knitting machines. Usefulness. An engineering method and algorithm for calculating the stresses in the needle of a knitting machine, which arises when it interacts with the knitting mechanism wedges, are proposed. It has been established that the life time of the needle can be increased by reducing the stiffness of the needle-wedge pair.